Talking About Type 2 Diabetes: Family Communication From the Perspective of At-Risk Relatives. (December 2015) - Myers, Melanie F.; Fernandes, Sara L.; Arduser, Lora; Hopper, Jennifer L.; Koehly, Laura M.
Purpose: The purpose of this study was to describe type 2 diabetes (T2DM) communication and risk reduction recommendations from the perspective of family members at risk for T2DM based on family history. Methods: Semistructured qualitative interviews were conducted with 33 individuals with a first-degree relative with T2DM. Participants were recruited from the community and a previous pharmacogenetics study. Deductive and inductive codes were applied to the transcripts. Results: Conversations with family members with and without T2DM focused on symptoms and disease management of the family member with T2DM. With at-risk relatives, conversations also focused on prevention. Lack of perceived relevance to family members without T2DM was a barrier to communication. Recommendations to facilitate communication included education of an at-risk family member to increase awareness of risk, followed by sharing of learned information with others. Conclusion: Efforts are needed to increase awareness and improve communication about T2DM risk factors, familial risk, and risk reduction behaviors within families with a family history of T2DM. Family members with and without T2DM should be encouraged to communicate with their relatives about T2DM and the risk to family members. Identification of family members who can facilitate communication, education, and modeling of healthy behaviors may increase awareness and motivate at-risk individuals to engage in risk-reducing behaviors.